2015
DOI: 10.1074/jbc.m115.653915
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Exonuclease TREX1 Is Also an Exoribonuclease That Acts on Single-stranded RNA

Abstract: Background: 3Ј repair exonuclease 1 (TREX1) is a DNase involved in autoimmune disorders and the antiviral response. Results: TREX1 also degrades single-stranded RNA or RNA in a RNA/DNA hybrid molecule. Conclusion: TREX1 is a human homolog of Escherichia coli RNase T. Significance: The novel RNase activity of TREX1 is crucial for understanding its physiological role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…For example, TREX1 has been shown to interact with PARP and facilitates its nuclear localization and activity35. In addition to ssDNA, TREX1 has now been implicated in the degradation of dsDNA and ssRNA3637. In fact, TREX1 has even been shown to have nuclease independent activities in the regulation of oligosaccharyltransferase that contributes to its role in immune regulation23.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TREX1 has been shown to interact with PARP and facilitates its nuclear localization and activity35. In addition to ssDNA, TREX1 has now been implicated in the degradation of dsDNA and ssRNA3637. In fact, TREX1 has even been shown to have nuclease independent activities in the regulation of oligosaccharyltransferase that contributes to its role in immune regulation23.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al verified this hypothesis and provided evidence for accumulation of ssDNA in Trex1 null mouse fibroblasts . Subsequent studies showed that TREX1 is not only a DNA exonuclease, but also functions as an exoribonuclease, indicating that mutations in TREX1 can also lead to accumulation of RNA along with DNA .…”
Section: Genetic and Molecular Mechanisms Underlying Agsmentioning
confidence: 94%
“…Additionally, it has been implicated in the regulation of BER through enhancing PARP1 [poly(ADP‐ribose) polymerase 1] activity. Moreover, TREX1 also possesses exoribonuclease activity and plays a role in the degradation of damaged tRNA substrates . Indeed, a large cohort of BER proteins have been implicated in RNA metabolism, and will be further discussed.…”
Section: Links Between the Ddr And Rna Metabolism Pathwaysmentioning
confidence: 97%
“…Moreover, TREX1 also possesses exoribonuclease activity and plays a role in the degradation of damaged tRNA substrates. 57, 58 Indeed, a large cohort of BER proteins have been implicated in RNA metabolism, and will be further discussed. Interestingly, very few DNA double-strand break (DSB) repair proteins have been reported to possess a dual role in post-transcriptional RNA metabolism, with the exception of RNF8 (ring finger protein 8) and BRCA1 (breast and ovarian cancer susceptibility gene 1).…”
Section: Links Between the Ddr And Rna Metabolism Pathwaysmentioning
confidence: 99%